Protection of Pertamina Logo Intellectual Property Rights against Brand Use outside the Collaboration Network - Saragih, Deardo Pieter; Ahmad Izzul Ramadhani; Rafy Naufal Padang Legrants (Westscience Press, 2024)
This research aims to show rights protection and sanctions for brand use outside the collaboration network. The research method used is normative legal research using a statute approach and a conceptual approach and analyzing by deduction. The results of this research show that the use of the Pertamina logo as a brand use or symbol outside the cooperation network is not permitted or violates the provisions and can be filed as a lawsuit or compensation by Article 83 of the Trademark and Geographical Indications Law. This is because the use of the Pertamina logo as a brand can only be used by the brand owner or other parties based on a written agreement (license). So the perpetrator can be subject to imprisonment for a maximum of 5 (five) years and/or a fine of a maximum of IDR 2,000,000,000.00 (two billion rupiah) because they have fulfilled the elements as intended in Article 100 paragraph (1) of the Trademark Law. and Geographical Indications. Apart from that, the perpetrator must also stop all actions related to the use of PT Pertamina's logo because they do not have legal rights to use the logo. If in this case the perpetrator does not stop all his actions, the brand owner can file a lawsuit in the form of a lawsuit for compensation and a lawsuit to stop all actions related to the use of the logo/brand as regulated in Article 83 paragraph (1) of the Trademark and Geographical Indications Law and the Directorate General of Property. Intellectuals will also reject the brand if the Pertamini business actor registers the brand.